Analisis Kelayakan Alternatif Investasi Pada UMKM Deily Roll Samarinda - Henry Tandy; Johan; Handi Wilujeng Nugroho (Scientific Literacy Innovation and Technology Journal, 2024)
On this day, the construction or establishment of a business is not unfamiliar thing. The establishment of a business is carried out to be able to increase income or what is commonly called to make a living. A business that is established can sell products or trending (unique). The problem discussed in this case study is whether the tow investment alternatives provided are feasible and profitable or not, and the choice of one of the alternatives that should be invested first based on the calculation of the investment feasibility analysis. The subject of this case study is Deily Roll. The purpose of this case study is to analyze the results of both investment alternatives and find out the best investment alternatives to invest in advance. The data collection techniques used are interviews and observations on gross income and case expenditures. The methods used to analyze the feasibility of investing are Net Present Value and Return on Investment. The results obtained from the investment feasibility analysis are the NPV value of the first investment alternative is Rp33.404.428,42 and the ROI value in 1 month is 36,09% and the NPV value of the second investment alternative is Rp35.111.428,42 and the ROI value in 1 month is 371,32%. The results show a conclusion that both investment alternatives are feasible and the second investment alternative or Tanita KD-400 food scales can be invested first.